Genetic diversity and population structure of Fasciola gigantica isolated from cattle in Malawi - Lenson Mogha; Henson Kainga; Nathan Kamanga; Thoko Flav Kapalamula; Catherine Wood; Lian F. Thomas; Florence Mutua; Neil Sargison; Kyoko Hayashida; Taiga Tsutsumi; Naoki Hayashi; Nariaki Nonaka; et al. (Veterinary Research Communications, 2025)

Representation of land–atmosphere coupling processes over Africa in coupled model intercomparison project Phase 6 - A. M. Mwanthi; J. N. Mutemi; E. Dyer; R. James; F. J. Opijah; T. Webb; F. Mutua; R. Washington; C. Senior; Z. Segele; G. Artan (Climate Dynamics, 2024)
Climate models are useful tools for monthly to decadal prediction of the evolution of climate. This study assesses how CMIP6 models represent soil moisture-latent heat regimes and coupling processes between the land and atmosphere. Metrics considered are terrestrial and atmospheric coupling indices to show the nature and strength of the coupling over Africa, focusing on the March to May (MAM) and June to August (JJA) seasons over East, Central, and West Africa. Characterization of the annual cycle indicates that model biases are highest during the peak of the rainfall season and least during the dry season, while soil moisture biases correspond with rainfall. Models show appreciable sensitivity to regional characteristics; there was model consensus in representing East Africa and the Sahel as regions of limited soil moisture, while major differences were noted in the wet regime over Central Africa. Most CMIP6 models tend to overestimate the strength of the terrestrial and atmospheric coupling pathways over East and Southern Africa. Inter-model differences in coupling indices could be traced to their inter-annual variability rather than the mean biases of the variables considered. These results encourage further advancement of land surface schemes in the next generation of climate models for a better representation of climate over Africa.

An overview of animal health and communication constraints in smallholder farming systems of Machakos County, Kenya - F. Mutua; J. Onono; A. Bruck; L. Makau (Tropical Animal Health and Production, 2019)

Postharvest processes of edible insects in Africa: A review of processing methods, and the implications for nutrition, safety and new products development - C. Mutungi; F. G. Irungu; J. Nduko; F. Mutua; H. Affognon; D. Nakimbugwe; S. Ekesi; K. K. M. Fiaboe (Critical Reviews in Food Science and Nutrition, 2019)